Two Centuries of International Migration - Joseph Ferrie; Timothy J. Hatton (Institute for the Study of Labor (IZA), 2013)
This is a draft chapter for B. R. Chiswick and P. W. Miller (eds.) Handbook on the Economics of International Migration. It provides an overview of trends and developments in international migration since the industrial revolution. We focus principally on long-distance migration to rich destination countries, the settler economies in the nineteenth century and later the OECD. The chapter describes the structure, direction and determinants of migration flows and the assimilation experience of migrants. It also examines the impact of migration on destination and source countries, and explores the political economy behind the evolution of immigration policy. We provide an historical context for current debates on immigration and immigration policy and we conclude by speculating on future trends.
Keywords: F22; N30; N40; 330; international migration history; development of immigration policy